Implementation of Augmented Reality Integrated with Problem-Based Learning in Structural Physics to Enhance Students’ Risk Analysis Skills - Jeffrey Payung Langi (Information Technology Education Journal, 2025)
This study aims to examine the effectiveness of implementing Problem-Based Learning (PBL) integrated with Augmented Reality (AR) in improving students’ risk analysis skills in the Structural Physics course at the State Polytechnic of Ambon. The research background is grounded in the importance of active learning strategies and interactive visual tools in bridging abstract concepts such as stress, load, and potential structural failure. A quasi-experimental approach with a one-group pretest–posttest design was employed. The research subjects consisted of 30 fourth-semester students from the Civil Engineering study program. Data were collected through pretests and posttests, PBL activity observations, questionnaires on perceptions of AR, and learning documentation. The results indicate a significant improvement in students’ risk analysis skills after participating in PBL–AR-based learning. The t-test results showed a p-value < 0.05, while the N-Gain scores fell into the medium category across all aspects, including risk identification, stress evaluation, and mitigation strategies. Observations revealed active student engagement in all stages of PBL, and the questionnaire indicated positive perceptions toward AR, particularly regarding its usefulness and ease of use. These findings suggest that the integration of PBL and AR not only enhances cognitive learning outcomes but also strengthens students’ affective and social dimensions. This study recommends the broader application of the PBL–AR model in vocational engineering education as a strategy to produce adaptive, competent, and technologically literate graduates. The model is considered capable of addressing the challenges of modern engineering education, which demands strong conceptual understanding and high-level problem-solving skills